Réponses

2012-09-23T16:25:59+02:00

x+2=8                 x+2-2=8-2               x=2

 

x-5=0                  x-5+5=0+5              x=5

 

x-5=1                  x-5+5=1+5              x=6

 

-3x=6                  -3x/(-3)=6/(-3)       x=-2   

 

-2x=3                   2x/(-2)=3/(-2)       x=-3/2

 

3x+2=8                 3x+2-2=8-2

                           3x/3=6/3                x=2

 

-2x+2=5               -2x+2-2=5-2

                           -2x/2=3/2               x=3/2

 

-5x+1=-3              -5x+1-1=-3-1

                           -5/5=-4/5                x=-4/5

 

3x-5=1                  3x-5+5=1+5

                            3x/3=6/3                x=2

 

5x-1=-7                 4x+1-1=5+1+2x

                            5x-2x=6+2x-2x

                            3x/3=6/3                x=2

 

4x+5=-7-2x             4x+5-5=-7-5-2x

                             4x=-12-2x

                             4x+2x=-12-2x+2x

                             6x/6=-12/6           x=-2